Socio-Economic Factors Affecting the Income of Cassava Farmers in Karangjoho Village, Pengadegan District - Mohamad Ade Rafly; Djeimy Kusnaman; Indah Setiawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Farmers in Karangjoho Village have problems, namely the use of production inputs is not optimal, selling prices fluctuate, and access to markets is still closed. This problem causes farmers to obtain low yields and profits. This research aims to (1) determine the characteristics of cassava farmers, (2) find out the income of cassava farmers, and (3) find out the socio-economic factors that influence the income of cassava farmers in Karangjoho Village, Pengadegan District, Purbalingga Regency. The research was conducted January – June 2024 in Karangjoho Village. Sampling was carried out using the simple random sampling method. Data analysis used includes descriptive analysis and multiple linear regression analysis. The results of the research show that cassava farmers in Karangjoho Village, Pengadegan District, have a family of three dependents, are relatively old, have low education, have high experience, and have a farming family background. The average cassava farming income per hectare in one planting season is IDR 14,657,310, with an average income of IDR 24,130,921 and costs of IDR 9,473,611. Socioeconomic factors simultaneously influence farmer income. The factors of land area, selling price, capital, and total production partially have a significant effect on farmers' income, while the factors of education, experience, age, number of family dependents, family background, labor, income outside farming, and sources of capital do not partially have a real effect on the income of cassava farmers.